Sonic Hedgehog-associated medulloblastoma arising from the cochlear nuclei of the brainstem - Grammel, Daniel; Bueren, André von; Kool, Marcel; Rutkowski, Stefan; Pfister, Stefan; Schüller, Ulrich (Acta neuropathologica, 2012)
Medulloblastoma is a malignant brain tumor of childhood that comprises at least four molecularly distinct subgroups. We have previously described that cerebellar granule neuron precursors may give rise to the subgroup with a molecular fingerprint of Sonic hedgehog (Shh) signaling. Other recent data indicate that precursor cells within the dorsal brain stem may serve as cellular origins for Wnt-associated medulloblastomas. To see whether Shh-associated medulloblastomas are also able to develop in the dorsal brainstem, we analyzed two lines of transgenic mice with constitutive Shh signaling in hGFAP- and Math1-positive brainstem precursor populations, respectively. Our results show that in both of these lines, medulloblastomas arise from granule neuron precursors of the cochlear nuclei, a derivative of the auditory lower rhombic lip. This region is distinct from derivatives of precerebellar lower rhombic lip where medulloblastomas arise in mice with constitutive-active Wnt signaling. With respect to their histology and the expression of appropriate markers, Shh tumors from the murine cochlear nuclei perfectly resemble human Shh-associated medulloblastomas. Moreover, we find that in a series of 63 human desmoplastic medulloblastomas, 21 (33%) have a very close contact to the cochlear nuclei on MR imaging. In conclusion, we demonstrate that precursors of the murine rhombic lip, which either develop into cerebellar or into cochlear granule neurons, may give rise to Shh-associated medulloblastoma, and this has important implications for the cellular origin of human medulloblastomas.
Gesehen am 27.04.2018